MINAT LITERSI MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA STKIP PARIS BARANTAI - Sri Juniati; Normasunah Normasunah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
This research is motivated by the low interst of students of language education and Indonesian of Literature at the STKIP Paris Barantai in reading books of reference, scientific books can increase of students knowledge is included in the less of category. The aims of this research are 1) to find out the literacy interest of Indonesian language and literature of students. 2) the find out what are the factors that hinder the progress of student literacy. This study uses a survey method by distributing questionnaires to respondents. The population and sample in this study were students in the fourth and sixth semesters as many as 100 students. Based on the results of the study, it can be interpreted that the majority of students do not choose to spend their free time reading but take walks and other activities. This is done because it is caused by two factors, namely internal and external. Internal factors are: innate or talent, gender, health condition, mental state, habits. While external factors are: instant generation, use of gadgets, influence of social media, lots of entertainment (TV and Youtube), minimal reading facilities/media, influencer of games. Key words: minotory, literacy, students.